The role of innovative educational technologies in teaching foreign language - Yarmanov Fakhriddin Norboyevich (Genius Journals, 2022)
In the article the author tries to state the advantages of using different interactive methods in teaching French and considers it effective to use the methods stated in the article during the lesson.
Keywords: Language; teaching; different methods